What do Cochrane systematic reviews say about non-surgical interventions for urinary incontinence in women? - Costa, Anderson Adriano Leal Freitas da; Vasconcellos, Igor Martins; Pacheco, Rafael Leite; Bella, Zsuzsanna Ilona Katalin de Jármy Di; Riera, Rachel (São Paulo Medical Journal, 2018)
BACKGROUND: Urinary incontinence is a highly prevalent condition that impacts self-esteem and overall quality of life. Many non-surgical treatment options are available, ranging from pharmacological approaches to pelvic exercises. We aimed to summarize the available evidence regarding these non-surgical interventions. DESIGN AND SETTING: Review of systematic reviews, conducted in the Discipline of Evidence-Based Medicine, Escola Paulista de Medicina, Universidade Federal de São Paulo (EPM-UNIFESP). METHODS: A sensitive search was conducted to identify all Cochrane systematic reviews that fulfilled the inclusion criteria. Titles and abstracts were screened by two authors. RESULTS: We included 20 Cochrane systematic reviews: 4 assessing methods of vesical training, 3 evaluating pharmacological interventions, 4 studying pelvic floor muscle training approaches and 9 aimed at other alternatives (such as urethral injections, weighted vaginal cone use, acupuncture, biostimulation and radiofrequency therapy). The reviews found that the evidence regarding the benefits of these diverse interventions ranged in quality from low to high. CONCLUSIONS: This review included 20 Cochrane systematic reviews that provided evidence (of diverse quality) for non-pharmacological interventions for patients with urinary incontinence. Moderate to high quality of evidence was found favoring the use of pelvic floor muscle training among women with urinary incontinence. To establish solid conclusions for all the other comparisons, further studies of good methodological quality are needed.